Pengaruh Anxiety First Aid Dalam Upaya Menurunkan Kecemasan Pada Remaja - Susi Indah Sari; Besse Lidia (Jurnal Kesehatan Komunitas, 2026)
Anxiety is a common mental health problem among adolescents, particularly during periods of academic pressure. If not properly managed, anxiety can negatively affect academic performance and psychological well-being. This study aimed to examine the effect of Anxiety First Aid (AFA) in reducing anxiety levels in adolescent girls. research pre-experimental one group pretest–posttest design was used involving 52 final-year students of the D-III Midwifery Study Program at STIKES Mutiara Mahakam Samarinda. The AFA intervention was conducted for seven consecutive days and included deep breathing relaxation, five-finger hypnosis, and music therapy. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. The research showed a significant reduction in anxiety scores after the intervention (p < 0.001), with a mean decrease of 11.192 points. The effect size analysis indicated a large effect (Cohen’s d = 1.138). In conclusion, Anxiety First Aid is effective in reducing anxiety among adolescent girls and may be recommended as a practical and non-invasive psychosocial approach for early anxiety management. Therefore, it is recommended that Anxiety First Aid can be implemented as a simple and safe effort to help teenagers manage anxiety.